Biocontrol potential of Pasteuria penetrans, Pochonia chlamydosporia, Paecilomyces lilacinus and Trichoderma harzianum against Meloidogyne incognita - MUKHTAR, Tariq; ARSHAD HUSSAIN, Muhammad; ZAMEER KAYANI, Muhammad (Phytopathologia Mediterranea, 2012)
The root-knot nematode, Meloidogyne incognita, is a sedentary endoparasitic plant pathogen with a very wide host range, which causes annual crop losses amounting to millions of dollars. The small number of available nematicides and restrictions on the use of non-fumigant nematicides due to high toxicity to humans and non-target organisms hinder effective nematode control. A possible alternative to chemical nematicides is the use of biological control agents for the management of this nematode. In the present study, the efficacy of four biocontrol agents was tested against M. incognita at different doses. The biocontrol agents Pasteuria penetrans, Pochonia chlamydosporia, Paecilomyces lilacinus and Trichoderma harzianum were mass produced and mixed with the formalin sterilized soil at the rates of 2 × 103, 4 × 103, 6 × 103, 8 × 103, and 1 × 104 endospores/chlamydospores/cfu per g of soil. Okra seeds (cv. Sabz Pari) were sown in pots of soil amended with the different agents, and 10 d after emergence, the plants were inoculated with 2000 freshly hatched second stage juveniles of M. incognita. Data on plant growth parameters and nematode infestations were recorded 7 weeks after inoculation. The antagonists varied significantly in enhancing various growth parameters and reducing nematode infestations in a dose-responsive manner. Both P. penetrans and P. lilacinus were equally effective and caused maximum reductions in number of galls, egg masses, nematode fecundity and build up as compared with T. harzianum and P. chlamydosporia. Reductions in these parameters at the concentration of 8 × 103 were statistically similar with those caused at the concentration of 1 × 104 chlamydospores/ endospores/cfu. Our results indicate that application of antagonists can suppress galling and reproduction of M. incognita resulting in enhancement of plant growth.